Influence of the Thermal Transient Response of Thermoelectric Generators in Maximum Power Point Tracking Algorithms - Torrecilla, Marcos Compadre; Montecucco, Andrea; Siviter, Jonathan; Strain, Andrew; Knox, Andrew R (2023 13th European Space Power Conference (ESPC), 2023)
Thermoelectric generators (TEGs) are used in a wide range of applications to convert heat into electricity. Heat waste recovery systems or radioisotope thermoelectric generators (RTGs) are examples of such applications. In most scenarios, TEGs are operated with limited heat flux sources where the temperature difference across the TEG cannot be considered as constant due to the induced Peltier effect, which is considered as parasitic in electrical power generation systems. A proper understanding of the behavior of a TEG under constant, or limited, heat flux, along with the transient response to load changes, is fundamental for the development of optimal maximum power point tracking (MPPT) control techniques. Most MPPT control techniques developed for TEG applications optimize the power generated when the TEG operates under constant temperature gradient but are not optimized when the device operates under a limited heat flux. This paper presents the transient response of a TEG under constant heat flux conditions, which is used to build a model of the TEG. The model is then used to develop an MPPT algorithm that optimizes the generation of electrical power when operated with a limited heat source. This paper presents simulation and test results of the performance of the developed algorithm against two of the most widely used MPPT algorithms, perturb and observe (P&O) and fractional open circuit (FOV).